Ticlopidine Inhibits the Prothrombotic Effects of Thrombopoietin and Ameliorates Survival after Supralethal Total Body Irradiation - Mouthon, Marc-André; Gaugler, Marie-Hélène; Vandamme, Marie; Gourmelon, Patrick; Wagemaker, Gerard; Van der Meeren, Anne (Thrombosis and Haemostasis, 2002)
Thrombopoietin modulates the response of platelets to several agonists and, on the other hand, those agonists can be released following irradiation. Thus, we have determined the effects of thrombopoietin, on its own and in combination with ticlopidine, an anti-platelet drug, on platelet activation, thrombosis formation and survival of irradiated C57BL6/J mice. Administration of thrombopoietin 2 h after 9 Gy total body irradiation increased the 125I-fibrin deposition in mouse tissues and accelerated platelet consumption as revealed by an enhanced drop in platelet counts. Additionally, the number of activated platelets, i.e. those expressing P-selectin on their membrane, was higher in thrombopoietin-treated mice as compared to the placebo group, regardless ex vivo stimulation with agonists. These effects of thrombo-poietin on platelet activation and consumption were reduced when mice were pretreated with ticlopidine. The combination of ticlopidine with thrombopoietin almost fully promoted 180-day survival, reaching the same efficacy as bone marrow transplantation, while only 30% of the mice treated with thrombopoietin alone survived. In summary, thrombopoietin induces long term-mortality of irradiated mice probably through platelet-mediated thrombosis and thus, ticlopidine efficiently counteracts these adverse effects of thrombopoietin.
Keywords: Thrombopoietin; irradiation; thrombosis; platelet; ticlopidine